Hubungan Gaya Belajar dengan Hasil Belajar Peserta Didik Paket B di Homeschooling Pena Surabaya - Khofifah, Siti; Mardliyah, Sjafiatul (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2024)
This research discusses the relationship between learning styles and learning outcomes for Package B students at Homeschool Pena Surabaya. Learning styles influence learning outcomes, such as in mathematics and social studies. The aim of this research is to identify the relationship between learning styles and learning outcomes, especially in mathematics and social studies subjects at Homeschooling Pena Surabaya. This study uses a quantitative approach. The data collection techniques used in this research were questionnaires and documentation. Techniques for analyzing data are validity testing, reliability testing, and hypothesis testing using Spearman rank. The result of the data calculation is that the Sig. (2-tailed) 0.017. Sig value. (2-tailed) < 0.05, which means there is a significant relationship. between learning style variables and mathematics learning outcome variables. Sig. (2-tailed) 0.037. Sig value. (2-tailed) < 0.05 means there is a significant relationship between the learning style variable and the social studies learning outcome variable